Imaging phenotypic differences in multiple sclerosis: at the crossroads of aging, sex, race, and ethnicity - Nathoo, Nabeela; Neyal, Nur; Kantarci, Orhun H.; Zeydan, Burcu (Frontiers in Global Women's Health, 2024)
Clear sex differences are observed in clinical and imaging phenotypes of multiple sclerosis (MS), which evolve significantly over the age spectrum, and more specifically, during reproductive milestones such as pregnancy and menopause. With neuroimaging being an outcome measure and also a key subclinical biomarker of subsequent clinical phenotype in MS, this comprehensive review aims to provide an overview of sex and hormone differences in structural and functional imaging biomarkers of MS, including lesion burden and location, atrophy, white matter integrity, functional connectivity, and iron distribution. Furthermore, how therapies aimed at altering sex hormones can impact imaging of women and men with MS over the lifespan is discussed. This review also explores the key intersection between age, sex, and race/ethnicity in MS, and how this intersection may affect imaging biomarkers of MS.